Corrosion-and damage-resistant nitride coatings for steel - Ahmed, M.; Munroe, P.; Jiang, Z.; Zhao, X.; Wajrak, M.; Guo, H.; Rickard, William; Xie, Z. (Wiley-Blackwell Publishing, Inc., 2012)
Ceramic coatings of distinct microstructures, namely TiSiN and CrN, were deposited on tool steels. The corrosion resistance of the coated steels was measured. Following nanoindentation, immersion tests were conducted in 70% HNO3 solution for 96 h. Deformed CrN, where deformation occurred through shear sliding of columnar grains, was insensitive to corrosion attack. In contrast, open cracks formed in the indented TiSiN coating, serving as pathway for reactive agents to penetrate through the coatings. Finite element analysis was applied to evaluate the damage tolerance of the coatings and its impact on the corrosion resistance of the coated steels.